Design and improvement guidelines to promote wellbeing for patients and their family in government tertiary care hospitals - Chotirat, Jutamat; Prugsiganont van der Hoeven, Supuck; Waroonkun, Tanut (Frontiers in Built Environment, 2025)
This research aims to explore the factors related to the physical environment in outpatient departments (OPD) that influence the hospital design process in public hospitals in Thailand after the COVID-19 pandemic. Additionally, it seeks to establish design guidelines for preventing respiratory diseases. This is a qualitative study involving 50 participants, including 20 medical personnel and 30 patients and their relatives, based on the Clinic Design Post-Occupancy Evaluation Toolkit. Data collection was conducted in three stages: (1) observing the physical environment using a checklist derived from the Clinic Design Post-Occupancy Evaluation Toolkit, (2) conducting surveys using the Analytic Hierarchy Process (AHP) questionnaire, and (3) interviews to assess impacts on mental health and the prevention of airborne respiratory diseases. The AHP ranking results indicated that issues concerning space screening, furniture arrangement, ventilation, recreational reception areas, lighting, and space layout are concerns expressed by medical personnel, patients, and their relatives in the outpatient departments of both buildings. Thematic analysis of focus group discussions among medical personnel, patients, and their relatives identified three main factors and two design recommendations to help prevent the spread of COVID-19 and respiratory disease: (1) Improving the outpatient waiting area environment to reduce the spread of infectious diseases. (2) Enhancing space management and screening processes.